Influence of the number of sets at a strength training in the flexibility gains - Junior, R. S.; Leite, T.; Reis, V. M. (Journal of Human Kinetics, 2011)
The aim of this study was to investigate the effects of 10 weeks of strength training with different number of sets and their influence on flexibility of young men. Sixty men were divided into three groups as follows: group that trained 1 set per exercise (G1S), group that trained 3 sets per exercise (G3S) and control group (CG). The training lasted 10 weeks, totaling 30 training sessions. The training groups performed 8 to 12 repetitions per set for each exercise. The flexibility at Sit and Reach Test was evaluated pre and post-training. Both trained groups showed significant increase in flexibility when compared to pre-training and the G3S showed significant difference when compared to CG post-training. According to this study, the strength training carried out without flexibility training promotes flexibility gains regardless the number of sets.